Some methods for improving fodder by incorporating forage legumes in cereal cropping systems in the Nigerian sub-humid zone - Mohamed-Saleem, M.A.; Otsyina, R.M.; Kaufmann, Ralph R. von (International Livestock Centre for Africa, 1986)
Describes the design and potential application of some techniques to improve fodder in selected cropping patterns in the subhumid zone of Nigeria. Lists major crops cultivated in the SHZ. Presents the cropping patterns in Abet.